A multinuclear static NMR study of geopolymerisation. (September 2015) - Favier, Aurélie; Habert, Guillaume; Roussel, Nicolas; d'Espinose de Lacaillerie, Jean-Baptiste
Abstract: Geopolymers are inorganic binders obtained by alkali activation of aluminosilicates. While the structure of geopolymers is now well understood, the details of the geopolymerisation reaction and their impact on the rheology of the paste remain uncertain. In this work, we follow the elastic properties of a paste made with metakaolin and sodium silicate solution. After the first sharp increase of elastic modulus occurring a few hundred of seconds after mixing and related to the heterogeneous formation of an alumina–silicate gel with a molar ratio Si/Al < 4 located at the grains boundaries, we focus on the progressive increase in elastic modulus on a period of few hours during the setting of the geopolymer. In this study, we combine the study of rheological properties of the paste with 23 Na, 27 Al and 29 Si static NMR measurement in order to better understand the origin of this second increase in elastic modulus. Our results show that, after a few hours, Al and Na evolution in the liquid phase are concomitant. This suggests the precipitation of an aluminosilicate phase where Al is in tetrahedral position and Na compensates the charge. Furthermore, Si speciation confirms this result and allows us to identify the precipitation of a product, which has a chemical composition close to the final composition of geopolymer. This study provides strong evidence for a heterogeneous formation of an aluminosilicate glass directly from the first gel and the silicate solution without the need for a reorganisation of Gel 1 into Gel 2.